Le soulier de Satin de Paul Claudel vu par les théâtrants slovaco-tchèques - Šimková, Soňa (Verbum – Analecta Neolatina, 2009)
In this paper I consider two essays published in Revue d’Histoire du Théâtre in 2000 dealing with the subject of water in theatre and in the work of Paul Claudel. In particular, I am focusing on the staging of Claudel’s Soulier de Satin performed by the National Theatre in Prague in 1993 by a Slovak theatre team headed by director Roman Polák. I am considering his work within the context of one of his most appreciated productions of the last decade, Marivaux’s play La Dispute (1988). In this production Polák used real water. By using water on stage he initiated a choice of specific theatricality. For his production, Roman Polák employed Jean-Louis Barrault’s adaptation of Claudel’s play, but he did not accept his way of theatricality. Instead of watermimed and danced by a choir of ballet, Polák worked with real water on stage. This paper tries to search answers to these questions: what was the reason for such a choice, and why where such solutions part of contemporary theatre aesthetics?